Carbazole‐Containing Polymer‐Assisted Trap Passivation and Hole‐Injection Promotion for Efficient and Stable CsCu2I3‐Based Yellow LEDs (Adv. Sci. 27/2022). Issue 27 (23rd September 2022) - Ma, Zhuangzhuang; Ji, Xinzhen; Wang, Meng; Zhang, Fei; Liu, Zibin; Yang, Dongwen; Jia, Mochen; Chen, Xu; Wu, Di; Zhang, Yu; Li, Xinjian; Shi, Zhifeng; et al.
Abstract : Yellow Light‐Emitting Diodes This cover image illustrates vividly the strategy of polymer poly(9‐vinylcarbazole) (PVK)‐modified CsCu2 I3 emitter for high‐performance yellow light‐emitting diodes (LEDs). PVK modification has the advantages of simultaneously passivating grain boundary defects and promoting charge carrier injection, as demonstrated in article number 2202408 . Zhifeng Shi, Chongxin Shan, and co‐workers finally achieve yellow LEDs with a peak external quantum efficiency of 1.35% and a record half‐lifetime of 14.6 h.